The response of different fungicides against Lasiodiplodia pseudotheobromae causing dieback disease of cocoa through in vitro test. Issue 2 (July 2021) - Musdalifa; Asman, A; Rosmana, A
Abstract: Cocoa dieback, caused by Lasiodiplodia pseudotheobromae, one of the significant cocoa diseases, which is a new disease in South Sulawesi and it is considered to be one of the important diseases in the field. Fungicides are one of the main methods to manage the disease on cocoa in South Sulawesi. However, the appropriate fungicides remain unexplored. Also, there are no data available and registered on the efficacy of fungicides on Lasiodiplodia cocoa dieback. Five different fungicides were used with three different concentrations namely fipronil + thiophanate-methyl + pyraclostrobin (0.5; 5.0; 50) ml/liter, sulphur (0.2; 2.0; 20) gr/liter, carbendazim + hexaconazole (0.04; 0.4; 4.0) gr/liter, carbendazim (0.1; 1.0; 10) ml/liter, and difenoconazole + azoxystrobin (0.1; 1.0; 10)) ml/liter. The results showed that the effectiveness of fungicides inhibit mycelial growth of L . pseudotheobromae was varied on each active ingredient. Fipronil + thiophanate-methyl + pyraclostrobin, carbendazim + hexaconazole and carbendazim showed excellent performances, followed by sulfur and difenoconazole + azoxystrobin. Higher concentration indicated excellent inhibition, followed by recommendation concentration and lower concentration. Fungicides can potentially be an option for dieback disease control in cocoa production areas that are at high risk of cocoa dieback disease.